Investigations on Polymeric Nanoparticles for Ocular Delivery - Neeraj Mittal; Gurpreet Kaur (Advances in Polymer Technology)
In the present investigation, an attempt was made to formulate timolol maleate (TML) loaded polymeric nanoparticles of flax seed gum (FX) and chitosan (CH) for ocular delivery using ionic gelation method. The process of nanoparticle preparation was optimized using 2-factor, 3-level central composite experimental design. The optimal concentration of FX and CH that yielded nanoparticles with minimum particle size (267.06 ± 8.65 nm) and maximum encapsulation efficiency (74.96 ± 4.78%) was found to be 0.10% w/v and 0.08% w/v, respectively. The formulated nanoparticles revealed considerable bioadhesive strength and exhibited sustained release of drug in in vitro diffusion studies. The ex vivo transcorneal penetration study revealed higher corneal penetration of TML compared to marketed eye drops. The confocal scanning laser microscopy (CSLM) studies also confirmed the ability of nanoparticles to penetrate into deeper layers of cornea. The histopathological studies revealed corneal biocompatibility of nanoparticles. The nanoparticles were found to reduce the intra ocular pressure (IOP) in rabbits for prolonged period when compared to conventional eye drops. The results of the present study suggested a promising role of polymeric nanoparticles for ocular drug delivery in treatment of glaucoma.